2020
DOI: 10.1590/1678-4685-gmb-2019-0326
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible ABC transporters genetic variants influence the outcomes of a weight-loss diet in obese women?

Abstract: ATP-Binding Cassette (ABC) transporters are involved in cholesterol metabolism and their dysfunctions could lead to obesity-associated complications. It was investigated whether SNPs in the ABCA1 (rs1800977 and rs2230806), ABCA7 (rs2279796) and ABCG1 (rs692383 and rs3827225) genes can modulate the responsiveness of 137 obese women to a weight-loss dietary intervention. Thus, anthropometric and lipid profiles were collected at baseline and after nine weeks of a calorie-restricted diet of 600kcal per day and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Ganda et al showed that increased ABCA1-mediated cholesterol efflux evoked tubular cholesterol accumulation in patients with DKD [16]. ABCA1 is involved in highdensity lipoprotein cholesterol (HDL-C) biogenesis, and changes in ABCA1 structure and/or protein expression could alter metabolic disturbances [17]. The loci of the ABCA1 gene rs2230806 is located in the major extracellular rings of the ABCA1 protein, which have an important role in APO-I and cholesterol efflux [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ganda et al showed that increased ABCA1-mediated cholesterol efflux evoked tubular cholesterol accumulation in patients with DKD [16]. ABCA1 is involved in highdensity lipoprotein cholesterol (HDL-C) biogenesis, and changes in ABCA1 structure and/or protein expression could alter metabolic disturbances [17]. The loci of the ABCA1 gene rs2230806 is located in the major extracellular rings of the ABCA1 protein, which have an important role in APO-I and cholesterol efflux [18].…”
Section: Introductionmentioning
confidence: 99%